Social Equity Issues in the Distribution of Feed-in Tariff Policy Benefits : A Cross Sectional Analysis from England and Wales Using Spatial Census and Policy Data - Grover, David; Daniels, Benjamin (Elsevier, 2018)
The feed-in tariff has become a popular policy instrument globally for deploying clean energy, often involving substantial public spending commitments. Yet relatively little attention has been paid to how payments made under this policy type get distributed across socioeconomic groups. This paper links information on individual domestic photovoltaic (PV) installations registered under the feed-in tariff for England and Wales, to spatially-organised census data. This makes it possible to observe which socioeconomic groups are benefitting most and least under the policy. Comparing the observed benefit distribution to a counterfactual distribution of perfect equality, a moderate to high level of inequality is found. Cross-sectional regressions suggest that settlement density, home ownership status, physical dwelling type, local information spillovers, and household social class shaped this outcome. Greater sensitivity to these factors in policy design could improve distributional outcomes under feed-in tariff policies in England and Wales, and beyond.